Legal Protection of Telemedicine Consumers: an Analysis of the Consumer Protection Act and Health Regulations in Indonesia: Perlindungan Hukum bagi Konsumen Telemedisin: Analisis Undang-Undang Perlindungan Konsumen dan Peraturan Kesehatan di Indonesia - Seliana, Irma; Prima Anggriawan, Teddy (Perspektif Hukum, 2025)
Telemedicine has become a fundamental part of modern healthcare delivery, transforming the contractual and liability relationships between healthcare providers and consumers. In Indonesia, the growing use of telemedicine raises complex issues in civil law, particularly concerning consumer protection, data privacy, and accountability for malpractice. This study aims to analyze the legal protection of telemedicine consumers under Indonesian law specifically Law No. 8 of 1999 on Consumer Protection, the Civil Code, and sectoral health regulations and to evaluate the civil liability of telemedicine providers when harm or loss occurs. Using a normative juridical (doctrinal) approach, this research employs statutory, conceptual, and comparative methods. The study reviews current laws such as the Health Omnibus Law (Law No. 17 of 2023), the Personal Data Protection Law (Law No. 27 of 2022), the Ministry of Health Regulation No. 20 of 2019 on Telemedicine, and Government Regulation No. 28 of 2024 as its implementing regulation. Findings indicate that Indonesia’s legal framework remains fragmented, with unclear boundaries between consumer law and health regulations. Comparative analysis with international standards reveals the need for a harmonized civil law framework to ensure accountability, guarantee patient rights, and strengthen consumer protection in digital health services.